A sustentabilidade do direito ao transporte no município de São Paulo: análise da legislação local - Barros, Fábio Nogueira (2019)
The city of São Paulo, Brazil's economy, culture and industry center, the largest city in the southern hemisphere, suffers from chronic urban mobility problems due to its large size and development history. This paper seeks to answer the presented hypothesis that there is no local incentive to sustainable transport as constitutionally required. For that, the hypothetical-deductive methodwas used, together with documentary analysis of local legislation, in particular thecity’s Master Plan and Mobility Plan,besides quantitative research on the evolution of municipal treatment regarding the issue of transportation of people and goods within its territory. The legal doctrine proves to be of great value for the validation of the analyzes of this great example of artificial environment, besides using the document creating the concept of sustainability, the report Our Common Future. It is concluded that São Paulo, despite the notorious transportation problems presented since the beginning of the XX century, has a robust legislation and municipal organization that lead towards sustainable urban mobility, with a view to the time necessary for this to occur, given the necessity of large investments required for its correct execution and of the time needed for the corrections and works to demonstrate their advantages.